2022
DOI: 10.3390/nu14071486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enterococcus faecium NCIMB 10415 on Gut Barrier Function, Internal Redox State, Proinflammatory Response and Pathogen Inhibition Properties in Porcine Intestinal Epithelial Cells

Abstract: In farm animals, intestinal diseases caused by Salmonella spp. and Escherichia coli may lead to significant economic loss. In the past few decades, the swine industry has largely relied on the prophylactic use of antibiotics to control gastrointestinal diseases. The development of antibiotic resistance has become an important issue both in animal and human health. The use of antibiotics for prophylactic purposes has been banned, moreover the new EU regulations further restrict the application of antibiotics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The significance was interpreted if the p-value fell below 0.05. To evaluate cell viability, IC ROS, IL-6/IL-8, and barrier integrity, six replicates per treatment group were utilized, while for adhesion inhibition determination, four replicates per treatment group were applied [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance was interpreted if the p-value fell below 0.05. To evaluate cell viability, IC ROS, IL-6/IL-8, and barrier integrity, six replicates per treatment group were utilized, while for adhesion inhibition determination, four replicates per treatment group were applied [46].…”
Section: Discussionmentioning
confidence: 99%
“…The viability of IPEC-J2 cells remained unaffected when subjected to a 10 8 CFU/mL concentration of L. rhamnosus suspension for 1 and 2 h, showing no significant alterations compared to the control group (Figure 2) [46].…”
Section: Cell Viability Determinationmentioning
confidence: 93%
“…The effect of Enterococcus faecium HDRsEf1 on IPEC-J2 cells has proven to be beneficial in many fields: enterotoxigenic E. coli -induced barrier impairment could be counteracted, E. coli adhesions were inhibited, and in addition E. coli -induced IL-8 secretion was modulated [ 41 ]. Furthermore, Enterococcus faecium NCIMB 10415 could reduce S. Typhimurium- and E. coli -induced ROS production in porcine intestinal cell culture (IPEC-J2) [ 45 ]. However, L. rhamnosus attenuated enterotoxigenic E. coli -induced damage to the IPEC-J2 cell barrier [ 46 ] and Lactobacillus amylovorus DSM 16698 inhibited enterotoxigenic E. coli adhesion to porcine epithelial cells (IPEC-1) and protected membrane damage induced by E. coli [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous investigation by Evivie et al [ 40 ] confirmed the medicinal usage of L. delbrueckii isolates as a probiotic against foodborne pathogens. Moreover, recent studies have evidenced the role of E. faecium as a promising probiotic candidate for both human and animal use [ 41 , 42 , 43 , 44 ]. Despite 16S rRNA being a very conserved region, six of our isolates revealed huge divergence in that region and this could be explained by the effect of environmental, demographic, genetic factors, and the maternal lifestyle on modifying the microbial diversity of human milk and infants’ gut [ 45 ].…”
Section: Discussionmentioning
confidence: 99%